2003
DOI: 10.1128/jvi.77.6.3470-3476.2003
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Infection and Replication in Normal Human Oral Keratinocytes

Abstract: Recent epidemiologic studies show increasing human immunodeficiency virus type 1 (HIV-1) transmission through oral-genital contact. This paper examines the possibility that normal human oral keratinocytes (NHOKs) might be directly infected by HIV or might convey infectious HIV virions to adjacent leukocytes. PCR analysis of proviral DNA constructs showed that NHOKs can be infected by CXCR4-tropic (NL4-3 and ELI) and dualtropic (89.6) strains of HIV-1 to generate a weak but productive infection. CCR5-tropic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
73
3
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 50 publications
4
73
3
2
Order By: Relevance
“…These findings are fully consistent with the results of other studies (70,71,132). However, Liu et al (61) have reported productive infection of oral keratinocytes with X4-and dual-tropic isolates (X4/R5) and minimal infection with R5 isolates. In contrast, Quinones-Mateu et al (91) could not demonstrate infection of oral keratinocytes with either X4 or R5 isolates.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings are fully consistent with the results of other studies (70,71,132). However, Liu et al (61) have reported productive infection of oral keratinocytes with X4-and dual-tropic isolates (X4/R5) and minimal infection with R5 isolates. In contrast, Quinones-Mateu et al (91) could not demonstrate infection of oral keratinocytes with either X4 or R5 isolates.…”
Section: Discussionsupporting
confidence: 83%
“…As well, detection of HIV-1 in oral mucosal cells was demonstrated by electron microscopy (91). Recent studies have demonstrated that oral keratinocytes can be infected by HIV-1 using galactosylceramide and CXCR4 as receptors (61), and ethanol may increase infectivity (23). As well, other studies have suggested that HIV-1 infection, both cell free and cell associated, of salivary gland cell lines via CXCR4 and CCR5 with a CD4-independent mechanism can be demonstrated in vitro (70).…”
mentioning
confidence: 99%
“…This result is in agreement with that of Quiñones-Mateu et al (42), who found no productive infection in normal oral keratinocytes inoculated with either X4 or R5 viruses. The findings, however, contrast with those of Liu et al (29), who showed infection of oral keratinocytes using high doses of X4 and R5/X4 viruses but not an R5 virus through a CD4-independent mechanism that may involve GalCer and/or CXCR4 as cellular receptors. In another study, Moore et al (35) showed infection of oral keratinocytes with cell-free R5 viruses but not X4 viruses.…”
Section: Discussioncontrasting
confidence: 56%
“…In another study, Moore et al (35) showed infection of oral keratinocytes with cell-free R5 viruses but not X4 viruses. The discrepancies may be due to variations in experimental conditions, such as the use of Polybrene during virus exposure by Liu et al (29) and differences in virus dosages and/or levels of cell surface GalCer, CCR5, and/or CXCR4 expression in the cell models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation